2015
DOI: 10.1017/s0007114514004383
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened beverages and risk of hypertension and CVD: a dose–response meta-analysis

Abstract: A number of prospective cohort studies have investigated the associations between consumption of sugar-sweetened beverages (SSB) and the risk of hypertension, CHD and stroke, but revealed mixed results. In the present study, we aimed to perform a dose -response metaanalysis of these prospective studies to clarify these associations. A systematic literature search was conducted using the PubMed and Embase databases up to 5 May 2014. Random-or fixed-effects models were used to calculate the pooled relative risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 34 publications
6
167
3
5
Order By: Relevance
“…Healthy beverage options such as water and fat-free or low-fat milk should be encouraged in place of SSBs. There is a robust body of evidence that SSB consumption is detrimental to health and has been associated with increased risk of CVD mortality, 58 hypertension, 59,60 liver lipogenesis, 61 T2DM, [62][63][64] obesity, and kidney disease. 65 Figure 3 illustrates the excessive intake of added sugars across the population.…”
Section: Limiting Alcohol and Sweets: Rationalementioning
confidence: 99%
“…Healthy beverage options such as water and fat-free or low-fat milk should be encouraged in place of SSBs. There is a robust body of evidence that SSB consumption is detrimental to health and has been associated with increased risk of CVD mortality, 58 hypertension, 59,60 liver lipogenesis, 61 T2DM, [62][63][64] obesity, and kidney disease. 65 Figure 3 illustrates the excessive intake of added sugars across the population.…”
Section: Limiting Alcohol and Sweets: Rationalementioning
confidence: 99%
“…The epidemiological relationships between SSB consumption, overweight, obesity, hypertension, and T2DM are strong (122). In a meta-analysis of prospective studies of SSB and hypertension, CHD, and stroke, the RR for a 1-serving increase in SSB/d was 1.17 (95 % CI 1.10, 1.24) for CHD and 1.08 (95% CI: 1.04 to 1.12) for incident hypertension, but no clear effect was seen for total stroke (RR 1.06, 95 % CI 0.97, 1.15) (123). A meta-analysis of seven cohort studies and five randomized controlled trials (RCTs) found SSB’s increased weight by 0.12 kg/serving/year (95% confidence interval [CI]: 0.10–0.14) in adults (124).…”
Section: Macronutrients Foods and Cvd Risk Factorsmentioning
confidence: 99%
“…The increase in resting heart rate after watermelon juice and placebo supplementation in this study is consistent with this interpretation. Given the increased stress placed on the cardiovascular system after watermelon juice consumption in this study, and the increase in coronary heart disease and hypertension morbidity associated with the consumption of sugar-sweetened beverages [59], longer term supplementation with a watermelon juice concentrate, at least in the form administered in this study, cannot be recommended.…”
Section: Discussionmentioning
confidence: 99%